2013
DOI: 10.4028/www.scientific.net/kem.586.178
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Interface of Heterogeneous Diffusion Welds of Titanium and Austenitic Steel

Abstract: Titanium is material which is used in many areas of human activity. Therefore it is necessary to join it with other material. It is very difficult to welding Ti with other metals by conventional fusion welding methods. There exist special joining technologies of heterogeneous materials which is possible to use. This is usually a joining of materials in the solid state, as diffusion welding, friction welding or explosion welding. This contribution deals with diffusion welding of titanium alloy Ti6Al4V and stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The laser weld joints became porous as a consequence of the Mg content and its evaporation, which caused the formation of gas bubbles and instability of the keyhole. Surface preparation decreases the hydrogen source, which causes porosity [62]. Xu et al observed that with the increase in shielding gas flow rate, the electron temperature of plasma plume increases in the maintenance phase.…”
Section: Appearance Of Laser Weldsmentioning
confidence: 99%
“…The laser weld joints became porous as a consequence of the Mg content and its evaporation, which caused the formation of gas bubbles and instability of the keyhole. Surface preparation decreases the hydrogen source, which causes porosity [62]. Xu et al observed that with the increase in shielding gas flow rate, the electron temperature of plasma plume increases in the maintenance phase.…”
Section: Appearance Of Laser Weldsmentioning
confidence: 99%
“…A possible reason for the formation of pores in the WM is the instability of the steam-gas channel during the welding process. Elements with a low melting point, in our case Mg, evaporate during laser welding and are trapped in the WM, promoting porosity formation [44]. According to Kuo et al [45], Al 2 O 3 is hygroscopic and absorbs ambient moisture.…”
Section: Computed Tomographymentioning
confidence: 84%
“…For AISI 304 steel, the diffusion zone width can generally be determined for temperatures (T) in the range of 1223.15 to 1423.15 K and for times (t) in the range of 1 to 5 h, according to Equation (19).…”
Section: Discussionmentioning
confidence: 99%
“…The largest differences were at 950 • C. Although the deviation from the real value seems to be quite high, the real difference in diffusion zone width at 950 • C is a maximum of 6.7 µm. (6) The diffusion zone width, and therefore the basic information for optimizing the interlayer thickness, can be determined with sufficient accuracy for AISI 304 steel generally for temperatures (T) in the range 1223.15-1423.15 K and for times (t) in the range 1 to 5 h according to Equation ( 18) and for AISI 316L steel according to Equation (19).…”
Section: Discussionmentioning
confidence: 99%